Risk of recurrent cervical artery dissection during pregnancy, childbirth and puerperium. (29th November 2014) - Reinhard, M.; Munz, M.; von Kannen, A.‐L.; Griesser‐Leute, H.‐J.; Dittrich, R.; Engelter, S. T.
<x xml:space="preserve">Abstract</x> Background and purpose Hormonal and mechanical factors might increase the risk for cervical artery dissection (CAD) during pregnancy and the puerperium. There is uncertainty how to counsel women with a previous CAD regarding the risk of CAD recurrence during pregnancy and the puerperium. Methods In an observational study of four stroke centers, all women aged 16–45 years with primary CAD in the previous decade were asked to participate in a standardized assessment on long‐term follow‐up with a special focus on pregnancies and recurrent CAD. Results Ninety‐two women were identified and 53 of them were included in the analysis (60%). Eleven women declined to participate, 28 were untraceable. The 39 non‐participants did not differ from participants regarding key baseline characteristics. Average follow‐up time was 72 months. Nine women (17%) had recurrent CAD after a median of 14 days (range 2 days to 117 months). Eleven women (20%) had a total of 13 completed pregnancies at a median of 44 months (range 12–84 months) after index CAD. Two of the pregnant women (18%) had suffered recurrent CAD ≥18 months prior to the pregnancy. All 13 pregnancies and puerperia went without recurrent CADs or cerebrovascular events. This includes giving birth by vaginal delivery (n = 6) and caesarean section (n = 7). None of the five women with typical connective tissue disease became pregnant. Conclusions Our observation suggests that the risk of recurrent CAD may not be greatly increased with pregnancies starting at least 12 months after CAD in women without typical connective tissue disease.